2013
DOI: 10.1103/physrevb.88.235415
|View full text |Cite
|
Sign up to set email alerts
|

Hanbury Brown and Twiss correlations in quantum Hall systems

Abstract: We study a Hanbury Brown and Twiss (HBT) interferometer formed with chiral edge channels of a quantum Hall system. HBT cross correlations are calculated for a device operating both in the integer and fractional quantum Hall regimes, the latter at Laughlin filling fractions. We find that in both cases, when the current is dominated by electron tunneling, current-current correlations show antibunching, characteristic of fermionic correlations. When the current-current correlations are dominated by quasiparticle … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…[33] for their case ν = 1/3 but not for ν ≤ 1/5, and it is in contrast with Refs. [35,37,38]. We suspect that this is somehow related to the different geometries involved, and we will investigate this issue in future works.…”
Section: Fractional Statistics Detection From Current-current Cormentioning
confidence: 91%
“…[33] for their case ν = 1/3 but not for ν ≤ 1/5, and it is in contrast with Refs. [35,37,38]. We suspect that this is somehow related to the different geometries involved, and we will investigate this issue in future works.…”
Section: Fractional Statistics Detection From Current-current Cormentioning
confidence: 91%
“…This interest is in part related to the bulkboundary correspondence, as edge transport reflects the topological nature of the bulk, revealing nontrivial properties unreachable through direct measurements. In particular, noise measurements in quantum point contact geometries (QPC) have been used experimentally to identify the fractional charge of the quasiparticle excitations in the bulk [12][13][14], and several proposals of more elaborate interferometric devices have been put forward as a way to probe their fractional statistics [15][16][17][18][19][20][21][22][23] with promising recent experimental results [24,25]. These considerations make the edge states of the FQHE a perfect testbed to examine delta-T noise.…”
mentioning
confidence: 99%
“…Effective attractive interactions may give rise to Cooper pairs, with the corresponding scattering manifested by bunch- ing. Anyonic quasi-particles have different statistics than either fermions or bosons [14,15,18]. In the present work we have shown that statistical transmutation can be engineered quantum mechanically without resorting to particle-particle interaction.…”
mentioning
confidence: 68%
“…Examples of emergent particles, whose quantum statistics differs from that of their constituents, range from Cooper pairs to fractional statistics anyons. The latter could be viewed as fermions with attached flux lines, in the fractional quantum Hall regime [14,15].…”
mentioning
confidence: 99%